2000
DOI: 10.1038/sj.mp.4000789
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the activities of erythrocyte free radical scavenging enzymes and the products of lipid peroxidation are increased in different forms of schizophrenia

Abstract: In order to examine antioxidant status and lipid peroxidation in schizophrenia patients, activities of three free radical scavenging enzymes (superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)), and the level of thiobarbituric acid-reactive substances (TBARS) as an index of lipid peroxidation have been studied in red blood cells. Schizophrenic patients were divided into three groups (disorganized (n = 21), paranoid (n = 26) and residual types (n = 18)) to determine differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
128
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(142 citation statements)
references
References 47 publications
10
128
3
1
Order By: Relevance
“…High-density polyunsaturated fatty acid (PUFA) is quite sensitive to free radicals. Increased lipid peroxidation reaction occurs and produces more LPO that damages the neuron membranes (Herken et al, 2001a;Yao et al, 2000a); this may explain the increased LPO level in the patient group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High-density polyunsaturated fatty acid (PUFA) is quite sensitive to free radicals. Increased lipid peroxidation reaction occurs and produces more LPO that damages the neuron membranes (Herken et al, 2001a;Yao et al, 2000a); this may explain the increased LPO level in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase (SOD), a key enzyme involved in the detoxification of superoxide radicals, has been consistently found increased (Vaiva et al, 1994;Yao et al, 1998b;Zhang et al, 2003a) in drug-free patients or those with TD (tardive dyskinesia) (Yao et al, 1998b;Zhang et al, 2003a), unchanged (Herken et al, 2001a) or decreased (Zhang et al, 2006) (Yao et al, 1998b) while unchanged (Yao et al, 1999) or decreased (Zhang et al, 2006) in chronic patients. Other antioxidant enzyme activity such as catalase (CAT) increased (Herken et al, 2001a) in different form of schizophrenia. And plasma proteins including albumin, uric acid and bilirubin in blood are reported lower in haloperidol-managed (Yao et al, 2000b) and first episode schizophrenic patients (Reddy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was shown that G72 genetic variation obviously modulates both the progressive brain changes that characterize schizophrenia (Hartz et al, 2010) and the reductions in temporal lobe and amygdala gray matter in people suffering from bipolar disorder (Zuliani et al, 2009). Furthermore, there is mounting evidence implicating mitochondrial defects and the resulting oxidative stress in the pathogenesis of schizophrenia (Altar et al, 2005;Herken et al, 2001;Mahadik and Mukherjee, 1996;Marchbanks et al, 2003;Prabakaran et al, 2004). Schizophrenic patients display a number of biomarkers indicative of increased oxidative stress, such as reduced GSH levels (Do et al, 2000), increased malondialdehyde levels (Zhang et al, 2006(Zhang et al, , 2007, and altered antioxidant enzyme activities (Gysin et al, 2007;Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%